Les métamorphoses de Joseph - Laurent Pietra (Carnets)
The different stories and works transforming the figure of Joseph, far from limiting itself to a mere literary imagination, renew the josephic counsel, where interpretation means survival and escaping from evil times. The present article intends to follow this long “tradition” and brings forward an advanced interpretation of the josephic texts.